2019
DOI: 10.1007/978-1-4939-9654-4_9
|View full text |Cite
|
Sign up to set email alerts
|

Site-Selective Functionalization of Nanobodies Using Intein-Mediated Protein Ligation for Innovative Bioconjugation

Abstract: with details of the nature of the infringement. We will investigate the claim and if justified, we will take the appropriate steps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…This strategy became available 30 years ago, applied to different recombinant proteins which require disulfide bonds to fold into their native structure and progressively improved with the introduction of more efficient strains such as Rosetta-gami B (DE3) or SHuffle T7 cells. These have been used for the cytoplasmic production of naked nanobodies [110,111] and of their fusion variants containing at their Cterminus an intein-chitin domain suitable for site-specific alkyne functionalization that requires reducing conditions for its functionality [109,112,113]. In one case it was confirmed that the binding properties of the non-modified nanobodies produced in the periplasm were preserved when the same binders were expressed as fusion reagents in the cytoplasm of Shuffle T7 cells [109].…”
Section: Bacterial Cytoplasmmentioning
confidence: 91%
“…This strategy became available 30 years ago, applied to different recombinant proteins which require disulfide bonds to fold into their native structure and progressively improved with the introduction of more efficient strains such as Rosetta-gami B (DE3) or SHuffle T7 cells. These have been used for the cytoplasmic production of naked nanobodies [110,111] and of their fusion variants containing at their Cterminus an intein-chitin domain suitable for site-specific alkyne functionalization that requires reducing conditions for its functionality [109,112,113]. In one case it was confirmed that the binding properties of the non-modified nanobodies produced in the periplasm were preserved when the same binders were expressed as fusion reagents in the cytoplasm of Shuffle T7 cells [109].…”
Section: Bacterial Cytoplasmmentioning
confidence: 91%
“…This relative difference in sizes affords a powerful benefit to the incorporation of synthetic handles onto proteins; the larger fragment (N or C, depending on the type of split intein) can be expressed heterologously, while the shorter fragment may be accessible to solid-phase peptide synthesis, obviating the limitations of metabolic incorporation of non-natural groups and making possible the installation of virtually any synthetic handle(s) or probe post-translationally . Owing to these powerful advantages, split inteins can be harnessed as a base platform toward the purification and functionalization of diverse proteins. , Specifically, early pioneering work by the Wood group led to the development of a pH-activatable intein cleavage system (a miniaturized Mtu-recA with a deleted endonuclease domain) for the purification of tag-free proteins, a thrust which has since improved substantially in scope and reaction profile with the discovery and evolution of newer and better-behaved canonically split intein systems (e.g., Npu DnaE). , In the same vein, such systems have also lent themselves well to a growing body of work targeting the C-terminal modification of different proteins with manifold handles, either through regular splicing or controlled cleavage through expressed protein ligation. , Summarily, while the literature is now rich in intein-based methods that enable the tagless purification and/or C-terminal modification of protein cargos, no such robust methodology has been developed for the single-step purification and N-terminal functionalization of proteins. This is an essential unmet need for cases where the C-terminus is necessary for protein function (e.g., Ubiquitin, Interferon-gamma, among others) or proves persistently refractory to post-translational modification.…”
Section: Introductionmentioning
confidence: 99%
“…33,34 In the same vein, such systems have also lent themselves well to a growing body of work targeting the C-terminal modification of different proteins with manifold handles, either through regular splicing 35 or controlled cleavage through expressed protein ligation. 36,37 Summarily, while the literature is now rich in intein-based methods that enable the tagless purification and/or C-terminal modification of protein cargos, no such robust methodology has been developed for the single-step purification and N-terminal functionalization of proteins. This is an essential unmet need for cases where the C-terminus is necessary for protein function (e.g., Ubiquitin, 38 Interferon-gamma, 39 among others) or proves persistently refractory to post-translational modification.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Furthermore, Nbs are usually well expressed in bacteria, are stable monomeric fragments with good thermostability (up to 90 °C), and have high solubility, resistance to pH changes, and are encoded by a gene fragment of around 360–380 bp, with the latter being a property that allows them to be engineered easily [ 23 , 27 , 28 , 29 , 30 ]. In addition, Nbs offer great potential for a variety of applications such as biosensors as well as contrast probes for fluorescent or MRI imaging owing to their strong binding affinity and specificity towards their cognate antigens [ 31 , 32 , 33 , 34 ]. Nevertheless, the selectivity and sensitivity of the detection of OC biomarkers remains the limiting factor for disease detection at an early stage and for monitoring treatment efficiency and recurrence.…”
Section: Introductionmentioning
confidence: 99%